2019
DOI: 10.1038/s41419-019-1739-2
|View full text |Cite
|
Sign up to set email alerts
|

The exosome-like vesicles from osteoarthritic chondrocyte enhanced mature IL-1β production of macrophages and aggravated synovitis in osteoarthritis

Abstract: Synovitis, a common clinical symptom for osteoarthritis (OA) patients, is highly related to OA pathological progression and pain manifestation. The activated synovial macrophages have been demonstrated to play an important role in synovitis, but the mechanisms about macrophage activation are still not clear. In this study, we found that the exosome-like vesicles from osteoarthritic chondrocytes could be a new biological factor to stimulate inflammasome activation and increase mature IL-1β production in macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 65 publications
0
113
0
Order By: Relevance
“…Then, the chondrocytes were cultured in a humidified atmosphere of 37˚C and 5% CO 2 in 5 ml dMeM (invitrogen; Thermo Fisher Scientific, inc.) supplemented with 10% FBS (Gibco; Thermo Fisher Scientific, Inc.) and 1% penicillin-streptomycin. lPS-stimulation of chondrocytes is an established cellular model for the study of oa (21,22). in the present study, when the cells reached 2x10 5 /well, chondrocyte apoptosis was induced by treatment with lPS (Sigma-aldrich; Merck KGaA) at a final concentration 5 µg/ml for 6 h (18).…”
Section: Methodsmentioning
confidence: 68%
“…Then, the chondrocytes were cultured in a humidified atmosphere of 37˚C and 5% CO 2 in 5 ml dMeM (invitrogen; Thermo Fisher Scientific, inc.) supplemented with 10% FBS (Gibco; Thermo Fisher Scientific, Inc.) and 1% penicillin-streptomycin. lPS-stimulation of chondrocytes is an established cellular model for the study of oa (21,22). in the present study, when the cells reached 2x10 5 /well, chondrocyte apoptosis was induced by treatment with lPS (Sigma-aldrich; Merck KGaA) at a final concentration 5 µg/ml for 6 h (18).…”
Section: Methodsmentioning
confidence: 68%
“…Nevertheless, an increasing number of studies have revealed that both ACVs and chondrocyte-derived exosomes could mediate cell-cell communication. [105][106][107][108][109] Exosomes from primary chondrocytes cultured in a normal environment (D0 exosomes) could restore mitochondrial dysfunction and enhance M2 macrophage penetration with a reduction in M1 macrophages. 106 The intra-articular administration of D0 exosomes efficiently delayed OA progression.…”
Section: Exosomes In Oamentioning
confidence: 99%
“…106 We found that exosome-like vesicles derived from osteoarthritic chondrocytes could stimulate inflammasome activation and increase mature IL-1β production in macrophages via the miR-449a-5p/ATG4B/autophagy pathway, which may aggravate synovitis and accelerate the progression of OA. 107 In addition, Chen et al reported that exosomes derived from chondrocytes (CC-Exos) could induce efficient ectopic chondrogenesis of cartilage progenitor cell (CPC) constructs in subcutaneous environments, which may represent a cell-free therapeutic approach for cartilage regeneration. 108 Moreover, chondrocyte-secreted exosomes could affect chondrogenic differentiation and cartilage matrix synthesis via the miR-95-5pregulated expression of HDAC2/8.…”
Section: Exosomes In Oamentioning
confidence: 99%
See 1 more Smart Citation
“…In one chip-assay study, 50 miRNAs were identified in exosomes in response to IL-1βstimulated SFB compared to in non-stimulated SFB, and among them, miR-4454 and miR-199b are related to inflammatory stimulation [18] and cartilage formation [19] , respectively. Ni et al found the exosome-like vesicles from IL-1β-pretreated chondrocytes could promote mature IL-1β production of macrophages [20] .…”
Section: Exosomes In Oa Pathologymentioning
confidence: 99%